Exploring system boundaries for green public-private partnerships - Liu, Jinchan; Chen, Chuan; Zhan, Wenting; Li, Xianhao (Journal of Civil Engineering and Management, 2025)
This study addresses the research gap in understanding the intricate dynamics of public-private partnerships (PPP) in fostering sustainable development by proposing a framework delineating eight system boundaries for green PPP. Through analysis across four cases from BRICS countries, the research illuminates the nuanced and interactive nature of these boundaries. The findings underscore the necessity of recognizing green PPP as complex socio-technical systems. The paper emphasizes the diversity and complexity of green PPP’s boundaries and highlights the importance of explicitly delineating them for meaningful comparison across contexts. By clarifying these perspectives, the study contributes to enhancing academic understanding and practical implementation of sustainable development initiatives through PPP.